2010
DOI: 10.1097/jto.0b013e3181d2f008
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Vascular Endothelial Growth Factor in Malignant Pleural Mesothelioma

Abstract: Our data suggest that the VEGF serum concentration could be a useful marker for screening MPM among asbestos-exposed individuals and as a prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 27 publications
2
36
0
2
Order By: Relevance
“…In esophageal, pancreatic and colorectal cancer, VEGF overexpression was significantly correlated with poor patient prognosis, in accordance with other malignancies (23,24). In malignant pleural mesothelioma, the serum level of VEGF has been reported to be significantly correlated with poor survival of patients (25). Our study revealed that in patients with stage III NSCLC, overexpression of VEGF-A in NSCLC tumor tissue was significantly correlated with a decreased 5-year survival rate.…”
Section: Discussionsupporting
confidence: 84%
“…In esophageal, pancreatic and colorectal cancer, VEGF overexpression was significantly correlated with poor patient prognosis, in accordance with other malignancies (23,24). In malignant pleural mesothelioma, the serum level of VEGF has been reported to be significantly correlated with poor survival of patients (25). Our study revealed that in patients with stage III NSCLC, overexpression of VEGF-A in NSCLC tumor tissue was significantly correlated with a decreased 5-year survival rate.…”
Section: Discussionsupporting
confidence: 84%
“…IL-8 is a member of the C-X-C chemokine family and has direct growth-potentiating and angiogenic effects on tumors. VEGF is a powerful mitogen for the vascular endothelium, and in patients with MPM, elevated serum levels of VEGF correlate with advanced disease stage and worse survival (45). It is reasonable to surmise that each of these factors has tumor-promoting effects in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of VEGF is one of the characteristics of MMs (18). We demonstrated that patients with malignant pleural mesothelioma had higher VEGF levels in pleural effusion and serum than a non-malignant population who had been exposed to asbestos (19,20). VEGF-receptor 1 (VEGF-R1), VEGF-R2 and VEGF-R3 are tyrosine kinase receptors for VEGF and are expressed in MM (18,21).…”
Section: Frequent Deletion Of 3p211 Region Carrying Semaphorin 3g Anmentioning
confidence: 97%